Isolation and Identification of some Bacterial Species From Cervix Infected Women in Salahuddin Governorate (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was carried out for isolating some pathogenic types of positive and negative bacteria for Gram stain, which cause the infection of the vaginitis in infected women and its diagnosis by routine laboratory methods and confirm the diagnosis using Vitek2compact system by collecting fifty samples of the swab of the cervix in the period between October 2015 till April 2016 from the in patients and out patients women in Salahuddin Hospital for the age groups between (14-50) years.The results of isolation show the percentage of bacterial growth was 78%, it reached samples in 78%.The results of the diagnosis of routine diagnostic tests, which were confirmed by using VITEK comparte2 system that there was a diversity of bacterial species including bacterial species from the source of isolation of vaginal infection, where the Escherichia coli bacteria had the highest isolation rate of isolation in 22%, followed by other bacterial species with different isolations. It was observed that there was a variation in the isolation rates and bacterial infections species of the vagina where bacterial isolates were isolated Proteus mirabilis isolates in 20.5% and as Klebsiella pneumonia showed isolations in 10.3%. For Salmonicida Aeromonas and Staphylococcus hominis Bacteria, the isolates was in 7.7%, While Pseudomonas luteola, Pantoes spp, Pseudomonas oryzihabitans, Ochrobactrum anthropic, Sphingomonas paucimbilis bacteria, isolations were isolated in 5.1 %.All isolates were characterized by their high resistance to ten different types of antibiotics, which represent: Gentamicin, Oxacillin, Tetracyclin, Cefotaxme, Amplicillin Novabiocin, Chloramphenicol, Rifampin, Trimethoprim and Azithromycin. The bacterial isolates gave absolute resistance to 100% of the majority of antibiotics used in our current study, while most isolates were sensitive to antagonists Gentamicin